Orphans (Ottoman Empire/Middle East) - Brand, Aaron (My University, 2014)
War, massacres, displacement, famine and economic crisis left over 100,000 children orphaned across the Ottoman Empire during WWI. Though most orphans were left to fend for themselves, as their numbers swelled, state and charitable groups began to set up orphanages, many of which were absorbed by Near East Relief after the war.
1914-1918-online. International Encyclopedia of the First World War
PUBLISHED
Keywords: Orphans; Near East Relief; First World War; World War I; Ottoman Empire; Middle east; Children; Atrocities & War Crimes in the First World War; FAMINE; First World War; Genocide; World War 1